Numerical Analysis of EPS Geofoam as Lightweight Embankment Fill on Soft Soil: Case Study of Patimban Access Toll Road, Package 3 - Akhmad Fauzi Al Afif; Yudhi Lastiasih; Herman Wahyudi (Interdisciplinary Social Studies, 2025)
The construction of the Patimban Port Access Toll Road faces significant geotechnical challenges due to the presence of thick soft soil layers characterized by low bearing capacity and high compressibility. Conventional soil embankments constructed on such ground conditions may induce excessive settlement and require a long consolidation period. This study aims to evaluate the effectiveness of Expanded Polystyrene (EPS) Geofoam as an alternative lightweight embankment material through numerical analysis using PLAXIS 2D. Four embankment configurations were analyzed: conventional embankment with initial preloading and composite embankments incorporating EPS Geofoam with thicknesses of 1 m, 2 m, and 3 m. The evaluation parameters include vertical settlement magnitude, consolidation time, and deformation patterns at key observation points, namely the center line, embankment toe, and critical settlement point beneath the embankment. The results indicate that the application of EPS Geofoam significantly reduces vertical settlement compared to the conventional embankment. Settlement reduction exceeding 85% was achieved for Geofoam thicknesses of 2 m and 3 m, accompanied by accelerated consolidation stabilization within less than 140 days. Increasing Geofoam thickness effectively reduces settlement but may induce uplift at the embankment toe due to lateral stress redistribution. Overall, EPS Geofoam with a thickness of 2–3 m provides the most optimal performance in controlling settlement and accelerating soil stabilization, making it a viable lightweight embankment solution for toll road construction on soft soil, particularly in coastal areas such as Patimban.